Analisis Determinan yang Mempengaruhi Penjualan Air Minum Isi Ulang pada Salah Satu Depot di Kelurahan Rappocini Kota Makassar - Talli, Abdul Safrin D; Rosdiana; Sulaiman (CV ODIS, 2024)
Sale represent the barometer of activity attainment in marketing procession by totally. A lot of factor becoming its consideration is consumer of before deciding to buy the goods among other things is product quality, price and form its promotion. So that this research is done as a mean to know the determinant factor influencing sale of drinking water refill at one of Depot in Chief Of Village of Rappocini of Town Makassar. Data obtained by propagating enquette to 95 customer, what is determined use the simple randomized sampling. Data obtained to be done by test of data quality of before analysed to use the doubled method regresi, test the parsial and determinasi. Result of research menunjukan that variable of product quality, price and promotion have an effect on positive and signifikan to sale of drinking water refill at one of Depot in Chief of village Rappocini of where variable of price have contribution to more dominant among other variable.